Today's Art of Japan '74. - Nakahara, Yusuke; Musée d'Art Contemporain, Montréal; Vancouver Art Gallery, Vancouver (Tokyo : Japan Art Festival Association, 1974)
Akimoto, Yukishige ; Aoyama, Koyu ; AY-O ; Baba, Kashio ; Domoto, Hisao ; Fukuda, Shigeo ; Furudate, Ko ; Hamaguchi, Yukio ; Hamano, Toshihiro ; Hasegawa, Makiio ; Hayashi, Takeshi ; Honda, Shingo ; Ida, Shoichi ; Ida, Yoshikuni ; Isaka, Yasuo ; Isono, Masahiko ; Kamatani, Shinichi ; Kanno, Seiko ; Kataoka, Tomokazu ; Kato, Tsuneaki ; Kawaguchi, Masahiro ; Kawaguchi, Tatsuo ; Kawai, Koji ; Kawamura, Chiaki ; Kimura, Kosuke ; Kitagawa, Kenji ; Kitamura, Kazuo ; Kobayashi, Nobuo ; Komoro, Itaru ; Kono, Michio ; Koura, Noboru ; Minami, Setsuko ; Mio, Kozo ; Miyazaki, Susumu ; Mori, Hideo ; Moriya, Yukiyoshi ; Nagai, Kazumasa ; Nagai, Keiko ; Nagasaki, Michihisa ; Nakano, Takeo ; Nimura, Yuko ; Noda, Tetsuya ; Oda, Mayumi ; Okabe, Kimihide ; Okada, Kenzo ; Onda, Shizuko ; Oshita, Kazuma ; Otsuka, Takashi ; Oura, Noboyuki ; Sakurai, Makoto ; Sato, Kiyoto ; Shigi, Go ; Shimizu, Momo ; Shimotani, Chiharu ; Soda, Minoru ; Suzuka, Yoshiyasu ; Takamatsu, Jiro ; Takeda, Shingo ; Tanabe, Kazuro ; Tanaka, Hideho ; Tasaki, Nobuo ; Tono, Juzo ; Toshima, Kazuko ; Ueda, Kaoru ; Wakae, Kanji W. ; Watanabe, Nobuhiko ; Yamai, Ikuo ; Yamamoto, Eishi ; Yashima, Masaaki ; Yasui, Yuji
biog. per kunstenaar
Engels
Today's Art of Japan '74, Musée d'Art Contemporain, Montréal, 8 Sept. - 6 Oct. 1974 ; Vancouver Art Gallery, Vancouver, Nov. - Dec. 1974
boek
Keywords: Japan